PHYSICAL FEATURES AND CRUDE FIBER CONTENT OF BANANA STEM SILAGE SUPPLEMENTED BY VARIOUS LEVELS OF KEMBANG TELANG (Clitoria ternatea) - ., Deswanto; Suarna, I W.; Suryani, N. N. (Jurnal Peternakan Tropika; Vol 8 No 2 (2020): Vol. 8 No. 2 Tahun 2020; Mei - Agustus, 2020)
This study aims to determine the level of addition of forage ( Clitoria ternatea ) on banana stem silage in terms of physical features and crude fiber content. Silage was made at the Farm of Sesetan Faculty of Animal Husbandry, Udayana University, Jl. Raya Sesetan, Gang Markisa, Denpasar. Analysis of physical features and crude fiber content was conducted at the Laboratory of  Animal Nutrition and Tropical Forage Science Faculty of Animal Husbandry Udayana University. The methot used a Completely Randomized Design (CRD) was used consisting of 4 treatments and 4 replications. Treatment A: 65% banana stem + 30% pollar + 5% (molasis + EM4), teratment B: 55% banana stem + 10% C. ternatea + 30% pollar + 5% (molasis + EM4), treatment C: 45% stem banana + 20% C. ternatea + 30% pollar + 5% (molasis + EM4), and treatment D: 35% banana stem + 30% C. ternatea + 30% pollar + 5% (molasis + EM4). The observed variables were that density, water absorption, water solubility and crude fiber content were as ovserved variables.The results showed that the real density (P<0.05) was higher in treatment D that was 0.17 g / ml compared to treatments A, B and C. The water solubility significantly (P<0.05) was higher in treatment D which was 48 , 38% compared to treatments A, B and C. The apparent water absorption (P<0.05) was higher in treatment A that was 232.26% compared to treatments B, C and D. The crude fiber content does not show a real different among all treatments.Based on the results of this study, it can be concluded that banana stem silage supplemented by 10-30% of forage flower ( Clitoria ternatea ) can increase density, water solubility and reduce water absorption and crude fiber content. For the optimal level supplementation of Clitoria ternatea that could improve the quality of banana stem silage not yet obtained. Key Words : silage, banana stems, kembang telang, physical properties, fiber content